2017
DOI: 10.3390/su9101828
|View full text |Cite
|
Sign up to set email alerts
|

Configurational Paths to Social Performance in SMEs: The Interplay of Innovation, Sustainability, Resources and Achievement Motivation

Abstract: In today's world of increasing ecological, social and economic issues, the question as to how businesses can become a vehicle towards more sustainable development has become more relevant than ever. Crucial to a more sustainable economy is the successful implementation of sustainable practices through entrepreneurial activities. Although there are attempts to describe how sustainable entrepreneurs differentiate themselves, the question of how some entrepreneurs manage to successfully create a sustainable enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 106 publications
1
36
0
5
Order By: Relevance
“…The aim of this research is to find causal patterns that explain the consumers' attitude toward EVs. Consequently, the fsQCA approach, which is able to find joint conditions that can explain a selected outcome, is used [73].…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…The aim of this research is to find causal patterns that explain the consumers' attitude toward EVs. Consequently, the fsQCA approach, which is able to find joint conditions that can explain a selected outcome, is used [73].…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Finally, we also propose to provide more joint analyses of entrepreneurs and investors concerning environmental, social, and sustainable business, e.g., through the use of configuration analyses (see e.g., [137]). It is important to analyse and compare their respective expectations from each other, joint goals, and the drivers of perceived risk, on the way to developing a more sustainable financial system.…”
Section: Conclusion: Relevance For Theory and Practice And Recommendmentioning
confidence: 99%
“…(b) On the other hand, a qualitative comparative analysis of fuzzy sets (fsQCA) was carried out because of their ability to adequately handle uncertainty and because they are suitable for studying social phenomena using small samples (Ragin, 2000(Ragin, , 2008. In addition, from the literature review we found an increasing number of papers using this data analysis technique (Fiss, 2007;Kraus et al, 2017;Huarng et al, 2020). This analysis enables us to: (1) overcome the problems associated with the minimum size of the sample (Rihoux and Ragin, 2004;Rihoux, 2006), (2) identify the effect of the combinations -configurations-of necessary and sufficient explanatory characteristics which other approaches are not able to adequately identify (Schneider and Wagemann, 2012), (3) offer a qualitative model based on set theory and logic (Thygeson et al, 2012), which complements quantitative techniques by modeling complex asymmetric relationships (Woodside, 2013) and, (4) allows to solve different types of problems (Huarng et al, 2020) as it allows to explain a result from the necessary or sufficient conditions (Ragin, 2000;Huarng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%